Assessing Physiological Responses: Exam Stress and Leukocyte Count in Medical Students at PUMHSW, Nawabshah - Rehnaz Shaikh; Uzma Riaz; Saba Leeza; Masood Nabi Noor; Hanna Khair Tunio; Javed Ahmed Lighari; Masood Ahmed Unar (ziauddin University, 2024)
Background: Medical students are confronted with substantial academic and psychological stressors during their education. Studies report that examination stress can have a noteworthy effect on the leukocyte count of students. This study aimed to evaluate the physiological effects of examination stress on the total and differential leucocyte cell count in medical students at Peoples University of Medical and Health Sciences for Women, Nawabshah. Methods: A cross-sectional comparative study was conducted from April to October 2019, with 110 MBBS students, divided into two groups of 55 students using a non-probability randomized sampling technique with first-year and second-year female students, whereas hypertensive, diabetic, and with any psychiatric disease were excluded. Blood samples were taken before and during the examination. Data were analyzed by SPSS version 23. All the continuous variables were analyzed by the t-test for Mean±S.D while all the numerical variables were analyzed by Student's t-test. Results: Pre-exam complete blood count (CBC) test reports of first-year students showed Neutrophils, Lymphocytes, Eosinophil, and Monocytes cell counts of 69.2182, 28.5455, 1.61, 1.2545 cell /microliter whereas complete blood count during exams showed 69.909, 27.9636, 1.41and 1.2000 cells/ microliter. In the second-year student, complete blood count before and during the exam showed Neutrophils 66.5273 to 64.0182, Lymphocytes 31.236 to 30.036, Eosinophil 1.92 to 1.76, and Monocytes 1.473 to 1.364 cells/microliter, the decreased values showing that there is an influence of exam stress on white blood cells. Conclusion: Exams in medical schools can be stressful enough to induce a substantial decrease in blood cell parameters among medical students.